Soybean: sustainability issues - Kumar, Pavan; Sharma, Manisha; Abubakar, Abubakar A.; Hayat, Muhammad Nizam; Ahmed, Muideen A.; Kaka, Ubedulla (Elsevier, 2023)
Soybean is the most abundant source of plant-derived protein and vegetable oil. Soy cultivation, is environmentally friendly than animal-based protein and the majority of common plant proteins, is associated with environmental damage than any other crop on the planet. This involves clearing forests for soy cultivation, soil erosion, greenhouse gases, water pollution and loss of biodiversity due to scale of production. Soy is a rich source of high-quality proteins, widely used as an important ingredient in preparation of meat products or plant-based meat analogs. Thus, the need to explore soy production sustainable becomes impeccable by improving agricultural practices, yield, proper certification, traceability and labeling of soy and its products, increase consumers awareness for acceptability and provide various financial and technological incentives.